A review of the records of Pachycheles rugimanus A. Milne-Edwards, 1880 (Crustacea: Decapoda: Anomura: Porcellanidae) from Brazil, with the description of a new species - Ferreira, Luciane Augusto De Azevedo; Tavares, Marcos (Zootaxa, 2019)
All previous records of Pachycheles rugimanus A. Milne-Edwards, 1880, from the Brazilian coast are reviewed and prove to represent a new species, P. coelhoi sp. nov. (from Amapá, northern Brazilian coast), and P. ackleianus A. Milne-Edwards, 1880, a species already known from Brazil (from Pará to Rio de Janeiro). The new species is described and illustrated, and compared to its most similar congeners: P. rugimanus and P. ackleianus from the western Atlantic, and P. velerae Haig, 1960, from the eastern Pacific (Galapagos Island and Cocos Island). Pachycheles coelhoi sp. nov. is distinguishable from the other three species by a suite of morphological characters, which include the ornamentation of the carapace and chelipeds, and the shape of the third thoracic sternite. All previous records of P. rugimanus from Brazil are considered invalid.